The Neurometabolic Function of the Dopamine–Aminotransferase System - Sergey A. Apryatin (Metabolites)
Background/Objectives: The neurometabolic function is controlled by a complex multi-level physiological system that includes neurochemical, hormonal, immunological, sensory, and metabolic components. Functional disorders of monoamine systems are often detected in clinical practice together with metabolic dysfunctions. An important part of the mentioned pathological conditions are associated with disturbances in protein metabolism, some of the most important biomarkers which are aminotransferases and transcription factors that regulate and direct the most important metabolic reactions. Another important part of energy metabolism is the dopamine-mediated regulation of protein metabolism. Methods: The review describes research results into the dopamine-mediated mechanism of metabolic regulation in humans and animals. Particular attention is paid to the neurometabolic mechanisms of protein metabolism. Results: The dopamine–aminotransferase system of the energy metabolism regulation is a separate, independent, regulatory and diagnostically significant biochemical pathway controlled by the hormonal system, the key hormone is cortisol, the key neurotransmitter is dopamine, the key transcription factor is CREB, and the key regulatory enzymes are alanine aminotransferase, aspartate aminotransferase, and tyrosine aminotransferase. Conclusions: This review presents an original study describing the discovery of a new regulatory mechanism for neurometabolic physiological function in humans and animals. A key part of this mechanism is the dopamine–aminotransferase system.